Polydopamine Enhanced Interactions of Graphene Nanosheets to Fabricate Graphene/Polydopamine Aerogels with Effectively Clear Organic Pollutants - He, Naipu (Langmuir : the ACS journal of surfaces and colloids, 2024)
Graphene/polydopamine aerogels (GPDXAG, where X represents the weight ratio of DA·HCl to GO) were prepared by the chemical reduction of graphene oxide (GO) using dopamine (DA) and l-ascorbic acid as reducing agents. During the gelation process, DA was polymerized to form polydopamine (PDA). The introduction of PDA in the gelation of aerogels led to a deeper reduction of GO and stronger interactions between graphene nanosheets forced by covalent cross-linking and noncovalent bonding including π-π stacking and hydrogen bonding. The weight ratio of DA·HCl to GO influencing the formation and morphology of GPDXAG was explored. With the increasing content of DA in gelation, the reduction of GO and the cross-linking degree of graphene nanosheets were enhanced, and the resulting GPDXAG had a more regular pore distribution. Additionally, introducing PDA into GPDXAG improved its hydrophobicity because of the adhesion of PDA to a network of aerogels. GPDXAG exhibited a higher removal efficiency for organic pollutants than the controlled graphene aerogels (GAG). Specifically, the adsorption capacity of GPDXAG for organic solvents was superior to that of GAG, and organic solvent was completely separated from the oil/water mixture by GPDXAG. The equilibrium adsorption capacity of GPDXAG for malachite green (MG) was measured to be 768.50 mg/g, which was higher than that for methyl orange (MO). In MG/MO mixed solutions, aerogels had obvious adsorption selectivity for the cationic dye. The adsorption mechanism of aerogels for MG was also discussed by simulating adsorption kinetic models and adsorption isothermal models